2021
DOI: 10.1007/s42087-021-00232-z
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic from the Health Workers’ Perspective: Between Health Emergency and Personal Crisis

Abstract: Different scholars have emphasised the psychological distress experienced by health workers during the COVID-19 pandemic; however, there are almost no qualitative studies and we know very little about the everyday experience of this group. The present study’s goal was to explore how health workers interpreted the meaning of the pandemic crisis in their life. An online survey was available during the Italian lockdown. Respondents were asked to write a passage about the meaning of living in the time of COVID-19.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Most frontliners (45.74%) reported that they were distressed by the heavy workload [ 17 , 26 ], whilst most non-frontliners (28.68%) did not perceive an increase in the level of distress since the beginning of the pandemic. However, they both reported negative emotions such as helplessness, restlessness, sadness, frustration and fear [ 5 , 6 , 7 , 14 , 18 , 19 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most frontliners (45.74%) reported that they were distressed by the heavy workload [ 17 , 26 ], whilst most non-frontliners (28.68%) did not perceive an increase in the level of distress since the beginning of the pandemic. However, they both reported negative emotions such as helplessness, restlessness, sadness, frustration and fear [ 5 , 6 , 7 , 14 , 18 , 19 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both the general population and medical staff developed a general sense of uncertainty and fear for the future [ 4 , 5 , 6 ]. In Italy, like elsewhere, the pandemic caused loneliness and fear of death, while also causing economic and social disruption [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, health facilities must provide measures capable of analyzing and regulating these conditions. It would be useful to introduce educational programs to improve and strengthen ways to proactively counter and regulate stress, resulting from workload and interpersonal relationships, during the pandemic (but it suffers for the lack of data proceeding the COVID-19 pandemic) [ 37 , 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%